PELATIHAN DASAR-DASAR KEAMANAN AIR BAGI PENGAWAS KOLAM RENANG (LIFEGUARD) Se-DIY - Susanto, Ermawan (Universitas Negeri Yogyakarta, 2009)
AbstractThe goal of this water safety training is to give basic skill and knowledgeabout water safety for 25 members of lifeguard in Special Province ofJogjakarta.The method that was used for this training were workshop, discussion,simulation, training in water, and evaluation test method. Evaluationwith direct observation consists of attention, willingness, enthusiasm to thematery who was given by society servants team (PPM), and post test for thelast. Then, evaluation in the pool with several activities that were helpingdrawning victims by equipment and no equipment, giving mouth to mouthbreath, cardiopolmunory respiration, bouancy test, diving test, and swimmingrescue. This training followed by 25 Jogjakarta’s lifeguards and theywere 2 from Sleman, 2 from Bantul, 8 from Jogja city, 6 from Gunungkiduland 5 FIK’s students.The result of discusion are (1) there are many swimming pool thatdon’t have rescue equipment like lifejacket, rope, stick, and wheel. (2) thereis less knowledge about rescue swimming technique for the lifeguard inJogjakarta., (3) there are many swimming pool which have no life guard, (4)we have high rate entusiasm of participant, and (5) we also have goodmanagement in swimming pool.Keywords: water accident, water safety, and life guard